Niesprężyste wyboczenie pręta przy krótkotrwałym obciążeniu - KORDECKI, Zbigniew (Engineering Transactions, 1966)
Inelastic buckling of a bar under short duration load The object of the considerations is a bar of small initial sinusoidal bend, loaded by a longitudinal, compressive, dynamic load of short duration. An approximate computation method is proposed, in which the bar is first considered to be elastic-plastic and, then, starting from the instant of the first occurrence of elastic strain (at middle span), rigid-plastic. The profile is assumed to be a perfect double tee profile. The minimum load producing a plastic hinge at middle span in the case of a suddenly applied constant load and a load linearly depending on time have been determined. The motion of a bar with one plastic hinge is analysed in the case of a constant load. The validity range of that scheme is determined as well as the type of behaviour of the bar in the plastic phase which follows. The accuracy of the method is estimated in an approximate manner. The procedure is illustrated by an example.